Outcomes Associated With the Adjunctive Use of Dipeptidyl Peptidase-4 Inhibitors With Insulin Versus Other Antihyperglycemic Medications in Patients With Prediabetes or Diabetes After Cardiac Surgery. (April 2021) - Clark, Lisa; Weeda, Erin; Griffin, Mary Lewis; Jones, Lee Ann; Haney, Jason
Background: Dipeptidyl peptidase-4 inhibitors (DPP-4i) plus basal insulin is noninferior to insulin monotherapy for glycemic control in medical–surgical patients, but data in postoperative cardiac surgery patients are sparse. Objective: To compare glucose control in postoperative cardiac surgery patients with prediabetes or diabetes receiving a DPP-4i plus insulin versus other antihyperglycemic regimens. Methods: We retrospectively identified patients with prediabetes or diabetes who underwent cardiac surgery at our hospital between May 2016 and June 2017. Included patients were stratified into cohorts: (1) DPP-4i plus insulin and (2) other antihyperglycemic regimens. Blood glucose levels were collected on postoperative days 2 to 7. Uncontrolled glucose (≥2 measurements <80 or >180 mg/dL in 1 day), hyperglycemia (>2 measurements ≥180 mg/dL in 1 day), and hypoglycemia (any measurement <70 mg/dL) were compared between cohorts using logistic regression adjusted for home antihyperglycemics. Results: We included 135 cardiac surgery patients, of which 65 received DPP-4i plus insulin. Eighty-two patients received antihyperglycemics at home. Uncontrolled glucose occurred in 61 (45.2%) patients; while hyperglycemia and hypoglycemia occurred in 50 (37.0%) and 24 (17.8%) patients, respectively. There was no difference in the adjusted odds of uncontrolled glucose (odds ratio [OR] = 1.43; 95% confidence interval [CI] = 0.65-3.11), hyperglycemia (OR = 1.20; 95% CI = 0.52-2.78), or hypoglycemia (OR = 0.69; 95% CI = 0.27-1.75) for those receiving DPP-4i plus insulin versus other regimens. Conclusion: Glucose control was no different among postoperative cardiac surgery patients receiving a DPP-4i plus insulin versus other regimens. DPP-4i use was not associated with hypoglycemia.